Patterns in Mobility and Modification of Middle‐ and High‐Latitude Southern Hemisphere Dunes on Mars. Issue 12 (26th December 2018) - Banks, Maria E.; Fenton, Lori K.; Bridges, Nathan T.; Geissler, Paul E.; Chojnacki, Matthew; Runyon, Kirby D.; Silvestro, Simone; Zimbelman, James R.
Abstract: Change detection analyses of aeolian bedforms (dunes and ripples), using multitemporal images acquired by the Mars Reconnaissance Orbiter High Resolution Imaging Science Experiment (HiRISE), can reveal migration of bedforms on Mars. Here we investigated bedform mobility (evidence of wind‐driven migration or activity), from analysis of HiRISE temporal image pairs, and dune field modification (i.e., apparent presence/lack of changes or degradation due to nonaeolian processes) through use of a dune stability index or SI (1–6; higher numbers indicating increasing evidence of stability/modification). Combining mobility data and SI for 70 dune fields south of 40°S latitude, we observed a clear trend of decreasing bedform mobility with increasing SI and latitude. Both dunes and ripples were more commonly active at lower latitudes, although some high‐latitude ripples are migrating. Most dune fields with lower SIs (≤3) were found to be active while those with higher SIs were primarily found to be inactive. A shift in prevalence of active to apparently inactive bedforms and to dune fields with SI ≥ 2 occurs at 60°S latitude, coincident with the edge of high concentrations of H2 O‐equivalent hydrogen observed by the Mars Odyssey Neutron Spectrometer. This result is consistent with previous studies suggesting that stabilizing agents, such as ground ice, likely stabilize bedforms and limit sediment availability. Observations of active dune fields with morphologies indicative of stability (i.e., migrating ripples in SI = 3 dune fields) may have implications for episodic phases of reworking or dune building, and possibly geologically recent activation or stabilization corresponding to shifts in climate. Plain Language Summary: Dune fields and sand sheets, very similar to those we see on Earth, are observed on the surface of Mars. Their presence attests to the importance of wind‐driven activity in shaping the Martian surface. Using repeated high‐resolution imaging with the HiRISE (High Resolution Imaging Science Experiment) camera in orbit around Mars on the Mars Reconnaissance Orbiter spacecraft, we can now look closely at dunes and ripples (collectively referred to as bedforms) on Mars to find evidence of changes over time. Changes in or movement of the bedforms indicate where they are currently active and migrating across the surface. Actively migrating bedforms provide valuable information about present‐day conditions on the surface such as sediment supply, wind speed, and wind direction. In this study, we investigated the activity of dunes and ripples in the middle and high latitudes of the southern hemisphere of Mars. We combined our results with those from investigations that looked at how the bedforms are degrading and being modified from nonwind‐driven processes, indicative of dune inactivity. Our results show that dunes and ripples are progressively less active and show increasing evidence of degradation and erosion with proximity to the south pole. In the northern part of our study area ( 40–55°S latitude), dune fields are mobile and are not degrading. Generally speaking, conditions where these dune fields formed, such as sediment supply and wind speeds, remain favorable for wind‐driven activity today. In the high southern latitudes (> 60°S), it appears that conditions favorable to dune field and sand sheet formation have shifted to less favorable conditions in most locations, perhaps episodically, since they originally formed. This shift in prevalence of active to apparently inactive bedforms and to dune fields that are more degraded occurs at roughly 60°S latitude and coincides with the edge of high concentrations of H2 O‐equivalent hydrogen observed by the Mars Odyssey Neutron Spectrometer and interpreted to indicate ice beneath the surface. Our observations of decreasing bedform mobility with increasing latitude support the accumulation of ground ice between dune sand grains, which may be stabilizing the grains and reducing sand availability in present climate conditions. Some dunes may be stabilized by ground ice at their core, while surface/near‐surface sediments, not cemented in the ground ice, continue to migrate as superposing ripples. Understanding the characteristics of the activity and morphology of dune fields can provide valuable insight into local and regional sedimentary and climatic histories on Mars and Earth. Our results may reflect more than one generation of dune building and possibly a current phase of episodic activity and may have implications for shifts in the climate to activate or stabilize dune fields and sand sheets over time. Key Points: The mobility of dunes and ripples decreases with increasing latitude and degradation for southern hemisphere Martian dune fields A marked shift toward reduced bedform activity and widespread dune degradation begins poleward of 60°S latitude Results support stabilization of sand sediments, likely by polar processes such as accumulating ground ice